The Influence Of Price And Quality On Farmers' Decision to Buy Tilapia Breeding From Pt Japfa In Panei Tongah Kab. Simalungun - Edison Sagala (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of price and product quality variables on the decision of farmers to buy tilapia seeds from PT Japfa in Panei Tongah Kab. Simalungun. The population in this study were farmers who bought tilapia seeds from PT Japfa in Panei Tongah Kab. Simalungun as many as 180 people and the sampling technique used is the Purposive sampling with 64 samples. The data technique used is by using a questionnaire and observation. The results of this study indicate that there is a significant influence between price and quality on breeders. Based on statistical data analysis, the variables in this study are valid and reliable. In the classical assumption test, the regression model is free of multicollinearity, does not occur heteroscedasticity, and is normally distributed. The regression equation obtained is Y= 12,408 + 464X1 + 412X2. With a coefficient of determination (R2) of 0.717. The value of Fcount for this study was 77.452 > Ftable 3.15 and the value of Tcount X1(5.223), X2(4.586) > Ttable 1.998. The results of the regression equation hypothesis test indicate that the price, quality variables have a significant effect on purchasing decisions.